Inside shadow banking: understanding the doomsday machine - Wesley C. Marshall (European Journal of Economics and Economic Policies: Intervention (EJEEP), 2014)
This article will argue that the shadow banking system has been at the heart of the Great Crisis since its first manifestations in the summer of 2007. This system has been purposefully misunderstood, as it is essentially a complex machine of too-big-to-fail banks designed to make large private profits while creating infinitely larger amounts of public debt. Years into the crisis, the shadow banking system still presents the greatest threat to global financial stability. As the fundamental operational conditions of this system gradually become clearer, and the understanding of the risks greater, a proper understanding of shadow banking is essential if the enormous problems of this doomsday machine are to be resolved.
Keywords: G01; G24; G15; 330; shadow banking; financial crises; investment banking; international financial markets